Insulated Solar Electric Cooking – Tomorrow's healthy affordable stoves?. (2017) - Watkins, T.; Arroyo, P.; Perry, R.; Wang, R.; Arriaga, O.; Fleming, M.; O'Day, C.; Stone, I.; Sekerak, J.; Mast, D.; Hayes, N.; Keller, P.; et al.
Abstract: We present a cooking technology consisting of a solar panel directly connected to an electric heater inside of a well-insulated chamber. Assuming continued decrease in solar panel prices, we anticipate that in a few decades Solar Electric Cooking (SEC) technologies will be the most common cooking technology for the poor. Appropriate use of insulation reduces the power demand making low-power Insulated Solar Electric Cooking (ISEC) systems already cost competitive. We present a 100 prototype and preliminary results of two implementations in Uganda.